THE IMPACT OF DUOLINGO TECHNOLOGY IN ENGLISH LANGUAGE LEARNING ON STUDENTS' ACHIEVEMENT - Mulyani, Marisa Sri; Suryadi, Suryadi (TELL - US JOURNAL, 2023)
Consequences of tech-Based Applications on English Learning a Language: A Case Study of Duolingo what part does technology play in the field pertaining to the English language learning has experienced a notable surge in importance within contemporary society. Duolingo provides a novel methodology for enhancing interactive and autonomous language acquisition. The utilisation technical means in language learning within the context of Indonesia presents a range of pertinent concerns. The primary objective of this study is to examine the influence of Duolingo technology on individuals' levels of English proficiency. The study additionally exhibits a profound dedication to meticulous research methodologies and ethical principles. Ensuring the respect of study participants' rights and security is achieved through the voluntary involvement of students and the acquisition of consent from the school. In summary, this study significantly enhances our comprehension of the correlation between the utilisation of technology in the context of English language acquisition and academic performance among high school students. The study employs a rigorous experimental methodology to establish a solid empirical basis for advocating the use of technology-based apps in the context of English language acquisition. The consequences of this phenomenon have the potential to influence educational policies and pedagogical approaches in order to improve students' competency in the English language, equipping them with the necessary skills to tackle future global challenges.